Między utopią a antyutopią : krytycznie o doktrynie Jana Jakuba Rousseau w świetle kontrowersji wokół jego poglądów na istotę woli powszechnej - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article is devoted to the controversy related to the interpretation of key concepts in the doctrine of one from among the most important thinkers of the eighteenth-century Europe — Jean-Jacques Rousseau. The considerations are carried out on many levels, focusing on the key concept of volonté générale in the treatise Du Contrat social ou principes de droit politique. The applied method, exegesis of the source text, corresponds with the polemic that has been conducted for decades, creating a rich literature on the subject. Selecting the positions of many distinguished researchers, the author attempts to confront Rousseau’s views with the flagship triad of basic values of the Great French Revolution: freedom, equality, and fraternity. This allowed the formulation of numerous comments, assessments, and opinions, at least some of which could be considered polemical or directly controversial.
Keywords: philosophy of law; political doctrines; Enlightenment; general will; social contract